2007
DOI: 10.1007/s00040-007-0959-0
|View full text |Cite
|
Sign up to set email alerts
|

Stable N-isotope signatures of central European ants – assessing positions in a trophic gradient

Abstract: Studies employing stable isotope technology have greatly contributed to understanding trophic relationships of tropical ants, but temperate-zone ants remain under-explored. We studied d 15 N values of 43 ant species from three subfamilies sampled across central Europe. After statistically accounting for the effects of elevation and geographical location of habitats, which alter the isotopic composition of nitrogen in ecosystems, significant patterns in N-isotope signatures were detected. These signatures hint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 53 publications
12
49
0
Order By: Relevance
“…Mean d 15 N-values of workers of most abundant species and Table 1 genera in Central Europe typically span a range of approx. 3 % in diverse dry grasslands (Sanders and Platner, 2007;Ó Grady et al, 2010) and other habitats (Fiedler et al, 2007). Similarly, in the dry grasslands mean d 13 C-values of workers also span a relatively small range of approx.…”
Section: Trophic Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Mean d 15 N-values of workers of most abundant species and Table 1 genera in Central Europe typically span a range of approx. 3 % in diverse dry grasslands (Sanders and Platner, 2007;Ó Grady et al, 2010) and other habitats (Fiedler et al, 2007). Similarly, in the dry grasslands mean d 13 C-values of workers also span a relatively small range of approx.…”
Section: Trophic Diversitymentioning
confidence: 99%
“…If trophic enrichment between tissues, species, and trophic levels is constant, a regression line between two components of sample sets is expected to have a slope of 1.0 and an intercept equal to the degree of fractionation. Fiedler et al (2007) studied 43 ant species in the European temperate zone and gained detailed insight into isotopic patterns of central European ants showing that trophobiosis is in fact an important form of nutrition for the ant genera Formica, Lasius, Camponotus, and Plagiolepis. Ottonetti et al (2008) successfully identified the food web position (d 15 N signal) and carbon sources (d 13 C signal) from lower level (like Homopteran tending) to high level (with predation) of five ant species in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…In temperate ant communities, the majority of species are omnivores, competing for the same resource pool of insect and plant matter (Vepsäläinen & Pisarski, 1982;Fellers, 1987;Hölldobler & Wilson, 1990;Retana & Cerdá, 1994;Morrison, 1996;Holway, 1999;Fiedler et al, 2007). They are also, with few exceptions, central-place foragers (Hölldobler & Wilson, 1990) that specialise on different components of foraging success, trading off between discovery (resource encounter) and dominance (resource harvest and control) abilities (Vepsäläinen & Pisarski, 1982;Fellers, 1987;Morrison, 1996;Davidson, 1998;Holway, 1999;.…”
Section: Introductionmentioning
confidence: 99%
“…Velasco Corona et al (2007) report that Liometopum appiculatum in Tlaxcala, Mexico, has a trophobiotic relationship with 14 species of Sternorrhyncha. The particularly high  15 N reported in L. microcephalum (albeit based on a sample from a single colony) compared to other ant species would indeed indicate a predominance of zoophagy in this species (Fiedler et al, 2007). However, contrary to the preceding claims of strict zoophagy in L. microcephalum, Wiest (1967) reports from a site in Austria that the trails of L. microcephalum also lead to bark aphids of the genus Stomaphis.…”
Section: Introductionmentioning
confidence: 62%